2019
DOI: 10.3961/jpmph.19.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy to Engage in Physical Activity and Overcome Barriers, Sedentary Behavior, and Their Relation to Body Mass Index Among Elderly Indonesians With Diabetes

Abstract: Objectives Elderly individuals with diabetes should maintain a normal body mass index (BMI) to help control their blood glucose levels. This study investigated barriers to physical activity (PA), self-efficacy to overcome those barriers, and PA self-efficacy among elderly individuals with diabetes in relation to BMI. Methods This cross-sectional study included 56 participants. Data were collected by a questionnaire interview and direct measurements for anthropometric da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The results of this study indicated that exercise self-efficacy has a significant positive predictive effect on adolescent PA, which is consistent with previous study findings [49,50]. Adolescents with better exercise self-efficacy participate in a higher level of PA. One previous study on the PA and exercise self-efficacy in 483 Spanish adolescents found a strong correlation between adolescent PA and self-efficacy [51]; in addition, Wing et al reported that self-efficacy was positively correlated with PA participation, in and out of school time, among 595 adolescents [52].…”
Section: The Influence Of Social Support and Exercise Self-efficacy Osupporting
confidence: 92%
“…The results of this study indicated that exercise self-efficacy has a significant positive predictive effect on adolescent PA, which is consistent with previous study findings [49,50]. Adolescents with better exercise self-efficacy participate in a higher level of PA. One previous study on the PA and exercise self-efficacy in 483 Spanish adolescents found a strong correlation between adolescent PA and self-efficacy [51]; in addition, Wing et al reported that self-efficacy was positively correlated with PA participation, in and out of school time, among 595 adolescents [52].…”
Section: The Influence Of Social Support and Exercise Self-efficacy Osupporting
confidence: 92%
“…This study involved secondary analysis of data previously collected for the purpose of measuring self-efficacy and overcome barriers to engage in physical activity, sedentary behavior, and their relation to body mass index among elderly Indonesians with diabetes ( Rachmah et al, 2019 ). This study expanded the analysis of previously published study ( Rachmah et al, 2019 ) and focused its analysis on the association between self-efficacy in physical activity and glycemic control among older adults with diabetes in Jagir Subdistrict, Surabaya, Indonesia. This study used quantitative approach with cross sectional study design.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming that diabetes prevalence in Indonesia was 2.5% ( Ministry of Health Republic of Indonesia, 2013 ), the minimum sample size calculated based on Charan and Biswas equation ( Charan and Biswas, 2013 ) was 38 persons. While using sample size calculation for difference in 2 independent proportions, and the minimum sample size required was 50 ( Rachmah et al, 2019 ). A larger sample size (N = 60) was recruited in order to achieve study power of 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have frequently documented that fatness and a higher body mass index (BMI) appear to be associated with lower self-efficacy ( Bagherniya et al, 2018 ; Rachmah et al, 2019 ; Schmidt and Pichler, 2020 ) in adolescents, especially in girls and that physical activity has the potential to stimulate positive behavior changes in this age group ( Kumar et al, 2015 ; D’Elia et al, 2020 ). Self-efficacy is defined as the belief that one has the ability to successfully engage in a specific behavior, and it is an important predictor of weight control and eating habits ( Bandura, 1997 ; Hopkins and Bennett, 2018 ).…”
Section: Introductionmentioning
confidence: 99%